Parasitic Motion and Workspace Analysis of Parallel Mechanism Based on 2-PRU/PUU - Chunsheng Ma; Jianguo Liu; Jie Wen; Yangtao He; Wenlong Fan (Jixie chuandong, 2022)
The Parasitic Motion and workspace of a new 2-PRU/PUU parallel mechanism are analyzed. Firstly， the degree of freedom of the mechanism is analyzed according to the spiral theory， and then the correctness of the results is judged by the modified Grübler-Kutzbach formula. Secondly， by establishing the kinematics mathematical model of 2-PRU/PUU parallel mechanism， the mathematical relationship between the Parasitic Motion and the position and pose of the moving platform is deduced. On this basis， the inverse position solution of the mechanism is calculated using the three-dimensional space coordinate vector method. Finally， the limit boundary search method is used to calculate the workspace in Matlab software， and Adams software is used to simulate the moving platform centroid motion parameters of 2-PRU/PUU parallel mechanism. The research provides theoretical and data support for scale synthesis， error analysis and practical engineering application of the mechanism.